Evaluation of efficacy between Amlexanox 5% oral paste & Triamcinolone Acetonide 3 oral paste in the treatment of recurrent aphthous ulcers: A Comparative Study - Molla, Nasir Uddin; Bhujan, Israt; Hossain, Shahadat; Wahab, Abdul; Nayeem, Abu (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll, 2011; 3 (1): 3-7 DOI: http://dx.doi.org/10.3329/jssmc.v3i1.12052